Pengaruh Penerapan Sistem E-Filing, Tingkat Pemahaman Perpajakan dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Rizqi Ilmiyah Sari; Nyimas Wardatul Afiqoh (Journal of Culture Accounting and Auditing, 2023)
This study aims to determine the influence of the application of the e-filing system, the level of understanding of taxation and taxpayer awareness on the compliance of individual taxpayers. The population in this study was all individual taxpayers in the city of Gresik, sampling using the random sampling method and the number of samples was 114 respondents. The results of this study indicate that the application of the e-filing system, the level of understanding of taxation and taxpayer awareness has a positive effect on individual taxpayer compliance. The study has limitations using only a small number of samples due to limited time for distributing questionnaires and researches can change the research variables and add the number of respondents to increase the number of samples so that further research can be better.